A special relativistic heat engine - William S. Cariens (International Journal of Mathematics and Mathematical Sciences)
This paper offers a marriage of concepts from both classsical thermodynamics and special relativity, thus forming a new part of modern thermodynamics. The main concepts taken from themodynamics and special relativity are those of a heat engine and E=mc2 respectively. Central to understanding the operation of this relativistic heat engine is the fact that upon heating a mass, its rest mass increases! This concept is nonexistent in classical thermodynamics. An increase in rest mass means that both the internal energy of a mass and its macroscopic kinetic energy increase!!!